2019
DOI: 10.3171/2018.8.jns181343
|View full text |Cite
|
Sign up to set email alerts
|

The relevant psychological burden of having a benign brain tumor: a prospective study of patients undergoing surgical treatment of cranial meningiomas

Abstract: OBJECTIVEMeningiomas are the most common intracranial neoplasm. Evidence concerning surgical management and outcome is abundant, while the implications for the quality of life (QOL) of a patient confronted with the diagnosis and undergoing surgery are unclear. The authors conducted a prospective study to evaluate QOL in relation to psychological comorbidities comorbidities.METHODSA prospective study of patients undergoing elective surgery for the removal of an intracranial meningioma was performed. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…In our study, the values of the physical health component of SF-36 were comparable to the values reported in meningioma patients before and after surgical treatment [13]. After meningioma surgery, patients generally report lower HRQoL compared to healthy controls [8,18], although some data on patients who underwent surgery for asymptomatic meningiomas demonstrated no significant difference compared to the general population [19,20].…”
Section: Patients' Quality Of Lifesupporting
confidence: 80%
See 2 more Smart Citations
“…In our study, the values of the physical health component of SF-36 were comparable to the values reported in meningioma patients before and after surgical treatment [13]. After meningioma surgery, patients generally report lower HRQoL compared to healthy controls [8,18], although some data on patients who underwent surgery for asymptomatic meningiomas demonstrated no significant difference compared to the general population [19,20].…”
Section: Patients' Quality Of Lifesupporting
confidence: 80%
“…A study examining patients with meningiomas and schwannomas of cerebellopontine angle under a watch-and-wait strategy reported clinically relevant levels of anxiety and depression in one-third of patients [16]. The proportion of anxiety and depression in our cohort was higher in comparison to comparison to other studies [12][13][14][15][16]. This might reflect some regional differences.…”
Section: Depression and Anxiety In Meningioma Patientscontrasting
confidence: 68%
See 1 more Smart Citation
“…We applied a similar methodology as studies concerning this topic previously published by our study group by prospectively screening patients scheduled for elective ACDF at our institution 19,20 . Our preoperative assessment encompassed various scales of depression and anxiety disorders, which we sought to identify via the following commonly employed psychological instruments: the Center for Epidemiological Studies Depression Scale 21,22 (Allgemeine Depressionsskala; ADS), Post-Traumatic Stress Scale-10 23 24 (STAI-T) and Anxiety Sensitivity Index-3 25,26 (ASI).…”
mentioning
confidence: 99%
“…Quality of life (QOL) as an important outcome measure has been studied recently with psychiatric correlates and cognitive functions, though research required for generating evidence-based clinical practice still remains inconclusive. [1516] Osoba et al . studied the effect of burden of the disease due to recurrence on QOL and found that the patients with glioblastoma multiforme or anaplastic astrocytoma had comparable QOL, though recurrent high-grade glioma had lower QOL scores than other localized ovarian and lung cancer.…”
mentioning
confidence: 99%